Platform workers centre stage! Taking stock of current debates and approaches for improving the conditions of platform work in Europe - Markus Elmer; Benjamin Herr; Dominik Klaus; Thomas Gegenhuber (Hans-Böckler-Stiftung, 2019)
A growing body of literature seeks to understand the conditions and consequences of platform work for platform workers and society at large. This study takes stock of current literature on platform work in Europe, discerns central debates (terms and definitions, relevance and diffusion, worker motivations and working conditions) and synthesizes knowledge on approaches for improving platform worker's conditions at different levels (worker, platform and regulatory level).
urn:nbn:de:101:1-2019102314232873398998
Keywords: 330; platform work; crowdwork; gig; crowdsourcing; crowd work